Impact of Copayment Changes on Children's Albuterol Inhaler Use and Costs after the Clean Air Act Chlorofluorocarbon Ban. (20th November 2016) - Galbraith, Alison A.; Fung, Vicki; Li, Lingling; Butler, Melissa G.; Nordin, James D.; Hsu, John; Smith, David; Vollmer, William M.; Lieu, Tracy A.; Soumerai, Stephen B.; Wu, Ann Chen
Abstract : Objective: To examine changes in children's albuterol use and out‐of‐pocket (OOP) costs in response to increased copayments after the Food and Drug Administration banned inhalers with chlorofluorocarbon (CFC) propellants. Setting: Four health maintenance organizations (HMOs), two that increased copayments for albuterol inhalers that went from generic CFC‐containing to branded CFC‐free versions, and two that retained generic copayments for CFC‐free inhalers (controls). We included children with asthma aged 4–17 years with commercial coverage from 2007 to 2010. Design: Interrupted time series with comparison series. Data: We obtained enrollee and plan characteristics from enrollment files, and utilization data from pharmacy and medical claims; OOP expenditures were extracted from pharmacy claims for two HMOs with cost data available. Findings: There were no significant differences in albuterol use between the group with increased cost‐sharing and controls with respect to changes after the policy change. There was a postpolicy increase of 6.11 OOP per month per child using albuterol among those with increased cost‐sharing versus 0.36 in controls; the difference between groups was significant ( p < .01). Conclusions: Increased copayments for brand‐name CFC‐free albuterol after the CFC ban did not lead to a decrease in children's albuterol use, but it led to a modest increase in OOP costs.